Paresthesia Predicts Increased Risk of Distal Neuropathic Pain in Older People with HIV-Associated Sensory Polyneuropathy. Issue 8 (10th February 2021) - Diaz, Monica M; Keltner, John R; Simmons, Alan N; Franklin, Donald; Moore, Raeanne C; Clifford, David; Collier, Ann C; Gelman, Benjamin B; Marra, Ph D, Christina; McCutchan, J Allen; Morgello, Susan; Sacktor, Ned; et al.
Abstract: Objective: Distal sensory polyneuropathy (DSP) is a disabling consequence of human immunodeficiency virus (HIV), leading to poor quality of life and more frequent falls in older age. Neuropathic pain and paresthesia are prevalent symptoms; however, there are currently no known curative treatments and the longitudinal course of pain in HIV-associated DSP is poorly characterized. Methods: This was a prospective longitudinal study of 265 people with HIV (PWH) enrolled in the CNS HIV Antiretroviral Therapy Effects Research (CHARTER) study with baseline and 12-year follow-up evaluations. Since pain and paresthesia are highly correlated, statistical decomposition was used to separate the two symptoms at baseline. Multivariable logistic regression analyses of decomposed variables were used to determine the effects of neuropathy symptoms at baseline on presence and worsening of distal neuropathic pain at 12-year follow-up, adjusted for covariates. Results: Mean age was 56 ± 8 years, and 21% were female at follow-up. Nearly the entire cohort (96%) was on antiretroviral therapy (ART), and 82% had suppressed (≤50 copies/mL) plasma viral loads at follow-up. Of those with pain at follow-up (n = 100), 23% had paresthesia at the initial visit. Decomposed paresthesia at baseline increased the risk of pain at follow-up (odds ratio [OR] 1.56; 95% confidence interval [CI] 1.18, 2.07), and decomposed pain at baseline predicted a higher frequency of pain at follow-up (OR 1.96 [95% CI 1.51, 2.58]). Conclusions: Paresthesias are a clinically significant predictor of incident pain at follow-up among aging PWH with DSP. Development of new therapies to encourage neuroregeneration might take advantage of this finding to choose individuals likely to benefit from treatment preventing incident pain.